A SIMPLE METHOD FOR PRODUCING AFLATOXIN B1 ON RICE MEDIUM FOR USE IN EXPERIMENTAL ANIMAL FEEDS - A. W. Yunus; J. Böhm (Journal of Animal and Plant Sciences, 2011)
A simplification and standardisation of the existing methods to produce aflatoxin B1 (AFB1) on rice medium is described. As per conventional method, rice were first soaked in 1 ml water/2 g of rice for 2 hr, autoclaved, and then inoculated with Aspergillus flavus. During different stages of incubation, water was added according to different regimens. It was concluded that 1 ml water/100 g of rice at 24 to 36 hr of incubation is the maximum amount of water that could be added for optimal AFB1 production.
Keywords: Aflatoxin; Rice; Aspergillus flavus